INTRODUCTION–Socially just plurilingual education in Europe: shifting subjectivities and practices through research and action. Issue 4 (2nd October 2021) - Erling, Elizabeth J.; Moore, Emilee
ABSTRACT: The articles in this special issue explore approaches to research and action in language education that have the potential to transform subjectivities and practices in relation to linguistic diversity. They seek ways within education and teacher education to overcome what Gogolin ([1994]. Der monolinguale 'habitus' der multilingualen Schule . Waxmann Verlag) called the 'mononlingual habitus', i.e. the deep-seated habit of assuming monolingualism as the norm for all individuals and thus for schooling. In doing so, the contributors aim to (re)inscribe multi/plurilingual education in Europe as a socially engaged pedagogical approach and field of research grounded in ideals of social justice. In this introduction, we provide a brief overview of multi/plurilingual education in Europe, linking to current critical work on neoliberalism, language, education and social justice. We then introduce and discuss some of the key theoretical concepts used by the different authors for studying subjectivities (e.g. attitudes, beliefs, ideologies, mind-sets) as well as the methodological approaches employed in the articles. We close with an overview of the different articles that make up the special issue and by highlighting some of the enduring issues in the field of multi/plurilingual education.